Decomposition Analysis for a Binary Choice Model - Myeong-Su Yun (Rutgers University, Department of Economics, 2000)
This paper introduces a new and simple decomposition method for a binary choice model that is equivalent to the Blinder-Oaxaca decomposition analysis for wage differentials. The decomposition method is first developed for a single probit model and later generalized to a simultaneous equations model. Using Taylor expansion, we approximate the differences in the probabilities of choosing option 1 over option 0 between two groups in order to find the effects of the differences in ``each'' individual characteristic and the differences in ``each'' coefficient. We implement this decomposition analysis studying the racial gap in female labor market participation rates. The racial gap of participation rates among women can be almost exclusively explained by the differences in the coefficients.
Keywords: C25; C35; J21; 330; decomposition analysis; selection bias; labor market participation; probit